Multi-Tiered System of Supports: An Ecological Approach to School Psychology Service Delivery. (January 2023) - Loftus-Rattan, Susan M.; Wrightington, Mahri; Furey, Jenlyn; Case, Jessica
Introduction: School psychologists work to support the academic, behavioral, and social-emotional well-being of students in schools. Their roles have become increasingly diverse in recent years due to the implementation of Multi-tiered System of Supports (MTSS) frameworks in schools throughout the United States. Statement of the Problem: Despite a national shortage of school psychologists, psychology students are often unaware of the profession or may have an outdated understanding of the role of school psychologists. Psychology students may also be unfamiliar with the MTSS framework, which promotes research-based, data-driven, equitable, and culturally responsive practices through a systemic, ecological approach to service delivery in schools. Literature Review: We review the main components of a typical MTSS prevention and intervention framework and describe the various roles of school psychologists and other key stakeholders within this model. Teaching Implications: This review and supporting resources can be used to introduce the field of school psychology to students. Additionally, it can be used to generate discussions regarding the provision of evidence-based and equitable academic and psychological services to students in the school through an ecological model. Conclusion: This article will help students gain an understanding of school psychologists' roles within a current MTSS educational service delivery model.